Libyan EFL Learners Motivation and Achievement in English Speaking Course in Higher Learning Institutions Using a Hybrid Problem-Based Learning (HPBL) Model - Eman Fathi, Baresh (Universiti Sains Islam Malaysia, 2024)
Proficiency in English speaking is one of the essential requirements for EFL learners to succeed academically and professionally. However, many Libyan undergraduate EFL learners commit various mistake in their English speaking which display their poor proficiency. The problems are attributed to various factors which include poor teaching method adopted by their teachers and the students’ lack of motivation. Therefore, this research explored the Hybrid Problem-Based Learning Model, (HPBL) a branch of Problem-Based Learning (PBL) approach, in motivating Libyan EFL learners in a speaking course. The research employed the case study research design in which several qualitative and quantitative data (i.e. observation, interview questionnaire, and audio-visual materials) were collected and analysed. The participants involved in the study are 30 first-year undergraduate students in one of the Libyan public universities. The study was conducted for a period of 9 weeks. Using the HPBL model the course was conducted alternatingly with traditional and PBL lessons. The first week was an introductory week (i.e. course overview, PBL introduction, Library orientation, and group formation). In the second week, the lesson was taught using traditional approach followed by the third week of PBL lesson and the rest of the weeks followed with the same alternation. Each of the PBL lesson plans were divided into 7 stages of in-classroom and out classroom activities based on Schmidt and Moust’s (1989) model of PBL “The Seven Jump”. At the end of each PBL lesson, students presented their possible solutions for the problem in a form of oral presentation (OP). The findings revealed that both the lecturer and the student participants had positive perceptions and experiences of the HPBL model such as the materials and process, the lecturers and students’ roles. The majority of the students have indicated moderate level of motivation to speak English after going through the HPBL model. Furthermore, the findings of the research revealed various factors that motivated the students to speak English language in the HPBL model. This includes familiarity with the given ’PBL cases, peer collaboration, tutor support, aفnd class presentation. These are the major findings which show that the HPBL model could be adopted to improve Libyan EFL learners’ speaking performance. Specifically, it is revealed that the HPBL improved the speaking ability of the students by enhancing fluency, grammar, comprehension, vocabulary, confidence level, intonation skills and pronunciation. Thus, the researcher recommends that HPBL model is a worthwhile model to be adopted in motivating and improving EFL students’ speaking ability in Libya.